2005
DOI: 10.1253/circj.69.78
|View full text |Cite
|
Sign up to set email alerts
|

Interval Representative of Transmural Dispersion of Repolarization in Children and Young Adolescents With Congenital Long QT Syndrome

Abstract: ong QT syndrome (LQTS) is a rare disorder characterized by prolonged ventricular repolarization and a high risk of cardiac events, including sudden cardiac death. 1,2 Among the mutations thus far identified in specific ion channel genes causing LQTS, 3-6 KCNQ1 and KCNH2 have been most commonly identified, and they are known to cause the LQT1 and LQT2 forms, respectively. Recent studies have reported that LQTS-related cardiac events tend to occur under specific circumstances in a genespecific manner. 7 In the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…5 Because of the important role of the autonomic nervous system, both as a modulator of the QT interval, and as a possible trigger of arrhythmia, several studies have assessed the use of different autonomic maneuvers in the diagnosis and management of LQTS. [6][7][8][9][10][11][12] However, genetic heterogeneity of the study populations, as well as methodological difficulties in assessing the complex relationship between rapid changes in HR and the QT interval duration make the interpretation of previous results or practical use of autonomic function tests difficult.…”
Section: Introductionmentioning
confidence: 99%
“…5 Because of the important role of the autonomic nervous system, both as a modulator of the QT interval, and as a possible trigger of arrhythmia, several studies have assessed the use of different autonomic maneuvers in the diagnosis and management of LQTS. [6][7][8][9][10][11][12] However, genetic heterogeneity of the study populations, as well as methodological difficulties in assessing the complex relationship between rapid changes in HR and the QT interval duration make the interpretation of previous results or practical use of autonomic function tests difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications showed that TpTe interval is longer in disorders such as long QT syndrome, polymorphic catecholaminergic ventricular tachycardia and Brugada syndrome. It may be also a predicting factor for elevated risk of sudden cardiac death in patients with heart disorders . It was demonstrated that the ratio of TpTe to QT interval is relatively constant, independent of the heart rate, and it may be a clinically useful marker of ventricular repolarization.…”
mentioning
confidence: 99%
“…3 Heterogeneous abbreviation of the action potential duration (APD) in different cell types spanning the ventricular wall seems to create the substrate for the genesis of ventricular arrhythmia in the short-QT syndrome, as is proposed for the long-QT syndrome and Brugada syndrome. [4][5][6][7][8] Brugada et al identified the first mutation associated with the short-QT syndrome. 3 The missense mutation (N588K) involving a substitution of lysine for asparagine in position 588 of KCNH2 was found to cause a remarkable gain of function in the IKr.…”
mentioning
confidence: 99%